2016
DOI: 10.1111/mec.13590
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the performance of DNA barcoding using posterior predictive simulations

Abstract: Accurate estimates of biodiversity are required for research in a broad array of biological subdisciplines including ecology, evolution, systematics, conservation and biodiversity science. The use of statistical models and genetic data, particularly DNA barcoding, has been suggested as an important tool for remedying the large gaps in our current understanding of biodiversity. However, the reliability of biodiversity estimates obtained using these approaches depends on how well the statistical models that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 97 publications
(172 reference statements)
1
32
0
Order By: Relevance
“…fasciatus complex) the number of clusters identified by the GMYC analyses was almost twice higher than NJ, suggesting a better capacity of this method in species separation. Some studies suggest that in complex groups the K2P model may underestimated the total number of clusters [79, 80]. Thus, we can suggest that herein GMYC, in general, was the better method for species separation.…”
Section: Discussionmentioning
confidence: 76%
“…fasciatus complex) the number of clusters identified by the GMYC analyses was almost twice higher than NJ, suggesting a better capacity of this method in species separation. Some studies suggest that in complex groups the K2P model may underestimated the total number of clusters [79, 80]. Thus, we can suggest that herein GMYC, in general, was the better method for species separation.…”
Section: Discussionmentioning
confidence: 76%
“…Pairwise genetic distances (Kimura 2‐parameter) among concatenated sequences were calculated using the DNADist program in phylip 3.69 (Felsenstein, ). Although use of the Kimura 2‐parameter model of evolution for genetic barcoding studies has been criticized (Srivathsan & Meier, ), simulations have suggested that it performs adequately when genetic divergence among sequences is low, as it is here (Barley & Thomson, ). mothur 1.29 (Schloss et al., ) was used to delimit MOTUs based on genetic distance thresholds of 0.1%–0.5% (McFadden, Brown, et al., ; McFadden, Reynolds, et al., ).…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate substitution model adequacy, Barley & Thomson () used posterior predictive simulations (Fig. , see Barley & Thomson for more details).…”
mentioning
confidence: 99%
“…To evaluate substitution model adequacy, Barley & Thomson () used posterior predictive simulations (Fig. , see Barley & Thomson for more details). The analysis of posterior predictive distributions is widely used in Bayesian statistics to assess model plausibility, but remains underused in phylogenetics or in ecology (but see e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation